Design, synthesis, and functional activity of labeled CD1d glycolipid agonists. - Jervis, P; Polzella, P; Wojno, J; Jukes, J; Ghadbane, H; Garcia Diaz, Y; Besra, G; Cerundolo, V; Cox, L (2013)
Invariant natural killer T cells (iNKT cells) are restricted by CD1d molecules and activated upon CD1d-mediated presentation of glycolipids to T cell receptors (TCRs) located on the surface of the cell. Because the cytokine response profile is governed by the structure of the glycolipid, we sought a method for labeling various glycolipids to study their in vivo behavior. The prototypical CD1d agonist, α-galactosyl ceramide (α-GalCer) 1, instigates a powerful immune response and the generation of a wide range of cytokines when it is presented to iNKT cell TCRs by CD1d molecules. Analysis of crystal structures of the TCR-α-GalCer-CD1d ternary complex identified the α-methylene unit in the fatty acid side chain, and more specifically the pro-S hydrogen at this position, as a site for incorporating a label. We postulated that modifying the glycolipid in this way would exert a minimal impact on the TCR-glycolipid-CD1d ternary complex, allowing the labeled molecule to function as a good mimic for the CD1d agonist under investigation. To test this hypothesis, the synthesis of a biotinylated version of the CD1d agonist threitol ceramide (ThrCer) was targeted. Both diastereoisomers, epimeric at the label tethering site, were prepared, and functional experiments confirmed the importance of substituting the pro-S, and not the pro-R, hydrogen with the label for optimal activity. Significantly, functional experiments revealed that biotinylated ThrCer (S)-10 displayed behavior comparable to that of ThrCer 5 itself and also confirmed that the biotin residue is available for streptavidin and antibiotin antibody recognition. A second CD1d agonist, namely α-GalCer C20:2 4, was modified in a similar way, this time with a fluorescent label. The labeled α-GalCer C20:2 analogue (11) again displayed functional behavior comparable to that of its unlabeled substrate, supporting the notion that the α-methylene unit in the fatty acid amide chain should be a suitable site for attaching a label to a range of CD1d agonists. The flexibility of the synthetic strategy, and late-stage incorporation of the label, opens up the possibility of using this labeling approach to study the in vivo behavior of a wide range of CD1d agonists.